2017
DOI: 10.5539/ijef.v9n5p58
|View full text |Cite
|
Sign up to set email alerts
|

Insider Trading and the Classification of Seasoned Equity Offerings: Evidence from Taiwan

Abstract: This paper investigates whether insider purchasing or selling before Season equity offerings (SEO) announcement have the impact on the cumulative abnormal returns (CAR) around SEO announcement in Taiwan. We find that there are negative announcement effects around the SEO announcement, which is not consistent with the argument that there are usually positive announcement effects around the SEO announcement in Taiwan. Moreover, long-run abnormal returns following SEOs are negative. Therefore, the motivation of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Jung et al (1996) found evidence that firms with inferior managerial ownership, who are arguably more susceptible to the agency problems described above, have more negative price reactions to announcing the issue of new shares. Huang and Chiu (2017) considered the impact of insider trading on SEO performance for the Taiwanese market and found that insider trading leads to overvaluation of SEO announcing firms, leading to negative abnormal returns after the announcement. In other words, the SEO announcement signals overvaluation of the firm rather than growth potential.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jung et al (1996) found evidence that firms with inferior managerial ownership, who are arguably more susceptible to the agency problems described above, have more negative price reactions to announcing the issue of new shares. Huang and Chiu (2017) considered the impact of insider trading on SEO performance for the Taiwanese market and found that insider trading leads to overvaluation of SEO announcing firms, leading to negative abnormal returns after the announcement. In other words, the SEO announcement signals overvaluation of the firm rather than growth potential.…”
Section: Literature Reviewmentioning
confidence: 99%